Diversity and expression of Plasmodium falciparum var gene in severe and mild malaria cases from Central India. (February 2021) - Bhandari, Sneha; Krishna, Sri; Patel, Priyanka P.; Singh, Mrigendra P.; Singh, Neeru; Sharma, Anjana; Bharti, Praveen K.
Highlights: "cys2/MFK*/*REY" motif with short length were restricted to cerebral and severe malaria. Higher expression level of var group A was associated with malaria severity. Peptide VAR P5 (DIGDIVRGKDLY) appeared to be a good marker for severity. Abstract: Background: Plasmodium falciparum erythrocyte membrane protein is encoded by a highly variable multicopy var gene family known to play a key role in malaria pathogenicity. Therefore, we investigated sequence variation, expression profile and immune response of the Duffy binding-like domain (DBLα) region of the var gene. Methods: Blood samples were collected from patients with cerebral, severe and mild malaria in Chhattisgarh, India, a region with endemic malaria. Polymerase chain reaction amplicons were cloned and sequenced to determine sequence variation. The expression level was analyzed targeting the upstream region of var gene using the Delta-Delta-Ct method. Immunoglobulin G (IgG) level was determined against the 6 synthetic peptides of the DBLα region. Results: The study identified that group 1 and group 5 sequences (cysteine/position of limited variability (cys/PoLV) classification) along with cys2/cys4 and MFK*/REY motifs and short amino acid length were significantly associated with malaria severity. The specific PoLV (MFKS, LREA, PTNL) were restricted to cerebral malaria. The expression level of var group A was higher than var groups B and C, demonstrating its prognostic characteristic. All peptides showed high-quality IgG response, while VAR P5 appeared to be a good marker for severity. Conclusions: The present study illustrates the presence of specific sequences of DBLα tags involved in severe malaria that could be targeted in future interventions for malaria control and elimination.